Different Aspects of the Interpretation of Accounting Policies in National and International Standards of Accounting - Zufarova Zilola Rakhim Kizi (Research Parks Publishers, 2022)
The article researched the methodological aspects of creating an accounting policy. As a result of research, different aspects of accounting policy interpretation in national and international accounting standards have been revealed.